Clonal diversity of MYC amplification evaluated by fluorescent in situ hybridisation and digital droplet polymerase chain reaction in oesophagogastric cancer: Results from a prospective clinical trial screening programme. (November 2019) - Davidson, Michael; Aronson, Lauren I.; Howard-Reeves, Julie; Bryant, Hanna; Cutts, Rosalind J.; Hulkki-Wilson, Sanna; Kouvelakis, Kyriakos; Kalaitzaki, Eftheleria; Watkins, David; Starling, Naureen; Rao, Sheela; Cardenosa, Marta Llorca; et al.
Abstract: Introduction: The MYC proto-oncogene is among the most commonly dysregulated genes in human cancers. We report screening data from the i MYC trial, an ongoing phase II study assessing ibrutinib monotherapy in advanced pretreated MYC- and/or HER2 -amplified oesophagogastric cancer, representing the first attempt to prospectively identify MYC amplifications in this tumour type for the purposes of therapeutic targeting. Methods: Screening utilising a fluorescent in situ hybridisation (FISH) assay for assessment of tumour MYC amplification has been instituted. An experimental digital droplet polymerase chain reaction (ddPCR) assay to assess MYC amplification in both tumour and circulating-tumour (ct)DNA has been developed and investigated. Results: One hundred thirty-five archival tumour specimens have undergone successful FISH analysis with 23% displaying evidence of MYC amplification. Intertumour heterogeneity was observed, with the percentage of cancer cells harbouring MYC amplification ranging widely between samples (median 51%, range 11–94%). Intratumoural clonal diversity of MYC amplification was also observed, with a significant degree of variance in amplification ratios (Bartlett's test for equal variance p  < 0.001), and an association between greater variance in MYC amplification and improved outcome with prior first-line chemotherapy. ddPCR was most accurate in quantifying MYC amplification in tumour-derived DNA from cases with a high proportion (>70%) of amplified cells within the tumour specimen but was not reliable in samples containing a low proportion of amplified cells or in ctDNA. Conclusions: Our results illustrate the utility of FISH to assess MYC amplification prospectively for a biomarker-selected trial by providing reliable and reproducible results in real time, with a high degree of heterogeneity of MYC amplification observed. We show that ddPCR can potentially detect high-level MYC amplifications in tumour tissue. Highlights: First prospective screening for MYC amplification in oesophagogastric cancer. MYC amplifications seen in 23% cases, with significant heterogeneity observed. Experimental ddPCR assay able to detect high-level tumoural MYC amplifications. Assessing MYC amplification for purposes of a biomarker-selected trial is feasible.